2020
DOI: 10.18203/2320-1770.ijrcog20204005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of teenage pregnancy and its obstetric and perinatal outcomes in a rural tertiary care hospital

Abstract: Background: Teenage pregnancy has been reported as one of the leading causes of death in adolescent girls in both developed and developing countries. In developed countries teenage pregnancies are most common in unmarried girls whereas in developing countries like India where early marriages are more common, teenage pregnancies are seen mostly in married women.Methods: In this retrospective observational study, data between January 2018 and December 2019 was studied; data was evaluated using MS excel for stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…11 Another retrospective study conducted by Mandala et al observed that 11.3% of deliveries were among women aged less than 20 years. 12 The prevalence in the present study is slightly lower than the NFHS data which may be due to the fact that the later consider both present and previous pregnancy at the time of survey and studies by Devi et al and Mandala et al are of relatively shorter duration and lesser sample than the present study.…”
Section: Discussioncontrasting
confidence: 75%
“…11 Another retrospective study conducted by Mandala et al observed that 11.3% of deliveries were among women aged less than 20 years. 12 The prevalence in the present study is slightly lower than the NFHS data which may be due to the fact that the later consider both present and previous pregnancy at the time of survey and studies by Devi et al and Mandala et al are of relatively shorter duration and lesser sample than the present study.…”
Section: Discussioncontrasting
confidence: 75%